The Art Ecocsystem of Gamelan Yuganada Community in Taman Kaja Village - Bhumi, I Made Bayu Puser; Mudra, I Wayan; Sariada, I Ketut (Gondang: Jurnal Seni dan Budaya, 2025)
Gamelan Yuganada, an art community based in Ubud, Bali, was founded in 2015 by I Wayan Sudirana with the aim of preserving Balinese gamelan while encouraging innovation through cross-disciplinary collaboration. This research aims to explain the activities of this group and map the art ecosystem that supports the preservation and development of their creativity. This study adopts a qualitative netnographic approach, conducting five months of digital participant observation on YouTube and Spotify, in-depth online interviews, and analysis of digital artifacts to uncover Gamelan Yuganada’s art ecosystem in the era of globalization. Data Analysis uses the theory of social practice by Pierre Boourdieou. The results of the study showed that Gamelan Yuganada was not only active in traditional performances but also created new compositions that combined traditional and contemporary elements. Various elements such as cultural, social, economic, legal, educational, and technological modalities have mutual implications for each other and form a good art ecosystem. Collaborations with various international artists and the use of digital technology are integral parts of the art ecosystem they build. The conclusion of this study emphasizes the importance of an adaptive and collaborative art ecosystem in maintaining the relevance of Balinese gamelan in the modern era, as well as providing a model for other art communities to develop works in a sustainable manner.